Modulatory effects of propolis samples from Latin America (Brazil, Cuba and Mexico) on cytokine production by human monocytes - Conti, Bruno José [UNESP]; Santiago, Karina Basso [UNESP]; Búfalo, Michelle Cristiane [UNESP]; Herrera, Yahima Frión; Alday, Efrain; Velazquez, Carlos; Hernandez, Javier; Sforcin, José Maurício [UNESP] (Oxford University Press (OUP), 2015)
Propolis has been used in folk medicine in different regions of the world including Latin America. Propolis is a resinous mixture of substances collected by honey bees from several botanical sources, and its composition contains a rich chemical variety, depending on the geographical area and plant sources. Our aim was to compare the modulatory effect of propolis samples from three different countries of Latin America (Brazil, Cuba and Mexico) on pro- and anti-inflammatory cytokine production (tumor necrosis factor (TNF)-α and interleukin (IL)-10, respectively) by human monocytes. Cells were incubated with propolis for 18 h at 37°C. Cell viability was assessed by 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide method, and cytokine production was determined by ELISA. All samples did not affect monocyte viability. Brazilian propolis stimulated both TNF-α and IL-10 production by monocytes. Cuban propolis stimulated TNF-α and inhibited IL-10 production, while Mexican sample exerted the opposite effect, inhibiting TNF-α and stimulating IL-10 production. The major compounds found in Brazilian, Cuban and Mexican propolis samples were artepillin C, isoflavonoids and pinocembrin, respectively. Brazilian, Cuban and Mexican propolis contained different components that may exert pro- and anti-inflammatory activity depending on concentration, what may provide a novel approach to the development of immunomodulatory drugs containing propolis.
Keywords: Cytokine; Monocyte; Propolis